2020
DOI: 10.1080/1331677x.2020.1831944
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management in V4 countries: the evidence of earnings smoothing and inflating

Abstract: Earnings management is one of the most challenging, debated and controversial topics in finance and financial management. Organisational, legislative, and social norms regarding the ethics of earnings management may vary significantly, with the views of top management and economic environment playing significant roles in shaping the organisational social norm. Thus, the aim of this research is to assess if earnings management is the common practice of enterprises within V4 countries. A novel approach of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 65 publications
0
57
0
3
Order By: Relevance
“…Callao et al (2017) tested thirteen models of accrual earnings management; their results in a sample of companies from the Visegrad Four indicate that although the modified Jones model is the most widely used model, there are other more reliable models such as Jones (1991) or Kasznik (1999). Nevertheless, a study by Kliestik et al (2020a) and Valaskova and Durana (2020) lean towards the generally preferred modified Jones model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Callao et al (2017) tested thirteen models of accrual earnings management; their results in a sample of companies from the Visegrad Four indicate that although the modified Jones model is the most widely used model, there are other more reliable models such as Jones (1991) or Kasznik (1999). Nevertheless, a study by Kliestik et al (2020a) and Valaskova and Durana (2020) lean towards the generally preferred modified Jones model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brzeszczynski et al (2011) pointed to discontinuity in earn-ings indicating the presence of earnings management practices, with a positive earnings threshold having significant implications for reported profits similar to those in US companies. Kliestik et al (2020a) revealed a growing trend of accounting manipulations in all Central European companies, with earnings reaching a threshold in 2014, 2013 (the Czech Republic) respectively. Cherkasova and Radasi (2017) comparing samples from Central and Eastern Europe also did not reveal any difference in earnings management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Manufacturing process monitoring systems have advanced as decentralized reconfigurable networked entities by use of cutting-edge intelligent machines. Sustainable manufacturing Internet of Things enables robust and dynamic planning and monitoring of production systems [165][166][167][168], by leveraging efficient and sound real-time data gathering, handling, and analysis from the industrial unit. Physical entities on the plant are self-governing intelligent logical units carrying out undertakings directed by distributed control functions.…”
Section: Discussionmentioning
confidence: 99%
“…The Polish environment, where there is also the highest number of studies published in the field of earnings management (Kliestik et al, 2021(Kliestik et al, , pp. 1452(Kliestik et al, -1470 is described by different earnings management practices across sectors, legal form (ownership structure) and firm age.…”
Section: Polandmentioning
confidence: 99%